LAPAROSCOPIC CHOLECYSTECTOMY: OUTCOME OF FIRST 202 CASES IN A DISTRICT HOSPITAL IN GILGIT - Haider, Ghulam; Hussain, Dildar; Waheed, Seema; Shah, Rahman; Khan, Ali Ahmad; Ibrahim, Mumtaz; Shah, Syed Mahboob Ali (Journal of Ayub Medical College Abbottabad, 2015)
Background: The incidence of gall stone disease is on the rise in Gilgit Baltistan. The objectives of the study were to assess the outcome of laparoscopic cholecystectomy in terms of conversion rate and postoperative morbidity, in The Aga Khan Medical Centre Gilgit. Methods: It was descriptive case series. All patients that underwent laparoscopic cholecystectomy between June 2009 to May 2014 were included. The data was collected prospectively. Demographic features, operative time, and hospital stay were studied. Postoperative complications were documented and evaluated according to outcome measures (bile duct injuries, morbidity, mortality, conversion rates, wound infections). Results: A total of 202 consecutive patients were enrolled with a mean age of 49±15 years. There were 164 (81%) female and 38(19 %.) male patients. Twenty nine (15%) patients had hypertension, 51 (25%) patients had diabetes mellitus as comorbid conditions. The mean operative time was 54±21 minutes. The operative time was longer in 52 (26%) patients. Three patients (1.5%) required conversion to open cholecystectomy due to obscured anatomy in the area of Calot’s triangle, and empyema gallbladder. The mean hospital stay was 2±0.7 days. No common bile duct injury, solid organ or bowel injury occurred in this study. The mean follow up duration was 30±15 months. Postoperative complications include, port site infection in 8 (2%) patient, chest infection in 5 (2.4%) patients, and one (0.5%) patient had myocardial infarction. There was no mortality reported in this group of patients. Conclusions: Laparoscopic cholecystectomy is a safe procedure with advantages of decreased wound infection, less pain, decreased hospital stay, and early recovery.